Identification of a PGXPP degron motif in dishevelled and structural basis for its binding to the E3 ligase KLHL12 - Chen, Z; Wasney, GA; Picaud, S; Filippakopoulos, P; Vedadi, M; D’Angiolella, V; Bullock, AN (Royal Society, 2020)
Wnt signaling is dependent on dishevelled proteins (DVL1-3), which assemble an intracellular Wnt signalosome at the plasma membrane. The levels of DVL1-3 are regulated by multiple Cullin-RING E3 ligases that mediate their ubiquitination and degradation. The BTBKelch protein KLHL12 was the first E3 ubiquitin ligase to be identified for DVL1-3, but the molecular mechanisms determining its substrate interactions have remained unknown. Here, we mapped the interaction of DVL1-3 to a ‘PGXPP’ motif that is conserved in other known partners and substrates of KLHL12, including PLEKHA4, PEF1, SEC31 and DRD4. To determine the binding mechanism, we solved a 2.4 Å crystal structure of the Kelch domain of KLHL12 in complex with a DVL1 peptide that bound with low micromolar affinity. The DVL1 substrate adopted a U-shaped turn conformation that enabled hydrophobic interactions with all six blades of the Kelch domain β-propeller. In cells, the mutation or deletion of this motif reduced the binding and ubiquitination of DVL1 and increased its stability confirming this sequence as a degron motif for KLHL12 recruitment. These results define the molecular mechanisms determining DVL regulation by KLHL12 and establish the KLHL12 Kelch domain as a new protein interaction module for a novel proline-rich motif.